2019
DOI: 10.1021/acscatal.9b01537
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Challenge of Computational Methods for Studying Mechanism and Reactivity in Homogeneous Catalysis

Abstract: Computational methods based on quantum mechanical modelling are increasingly used to provide insight into mechanistic aspects of homogeneous catalysis. While the potential and value of such methods is obvious, it is also clear that it remains challenging to obtain reliable and predictive mechanistic insights from modelling. In this perspective, we assess the various factors influencing the quality of computational studies. While the type of electronic structure theory methodology used is of course of great imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
176
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(181 citation statements)
references
References 76 publications
5
176
0
Order By: Relevance
“…Computational chemistry has become a powerful tool in homogeneous catalysis, and combined with experiments, delivers molecular models enabling the rational design of catalytic systems. [13][14][15][16][17][18][19][20][21][22] However, the key ligands and substituents of these models are classied with generic labels (e.g., 'strong p-acceptor', 'bulky' or 'proton-acceptor') that can be assigned to tens or hundreds of known compounds. The combination of all these possibilities yields a region of the chemical space 23 containing thousands of catalyst candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry has become a powerful tool in homogeneous catalysis, and combined with experiments, delivers molecular models enabling the rational design of catalytic systems. [13][14][15][16][17][18][19][20][21][22] However, the key ligands and substituents of these models are classied with generic labels (e.g., 'strong p-acceptor', 'bulky' or 'proton-acceptor') that can be assigned to tens or hundreds of known compounds. The combination of all these possibilities yields a region of the chemical space 23 containing thousands of catalyst candidates.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, recent analyses have highlighted that obtaining reliable and predictive mechanistic insight from modeling remains challenging. [ 1,2 ] As the kinetic and mechanistic features of reactions are best evaluated by using activation parameters, an adequate refinement of computational methods for evaluating them is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry has played a vital role in elucidating the mechanisms of organic reactions and helping design better catalysts and/or reactions [12][13][14][15][16][17][18][19][20] . Although many computational studies on the mechanism of DA and 1,3-dipolar cycloaddition reactions have been reported 3,4,6,[21][22][23][24][25][26] , computational works on the mechanism of HDA reactions are quite limited [27][28][29] .…”
mentioning
confidence: 99%